A Critical Assessment of Organic Agriculture in Portugal – A reflexion on the agro-food system transition - Salavisa, I.; Soares, M.; Bizarro, S. (5º Workshop - Dinâmicas Socioeconómicas e Territoriais Contemporâneas, 2020)
Over the last few decades, the organic agriculture sector has experienced sustained growth. Globally, as well as in The European Union and Portugal, organic production accounts for just under 10% of total Utilised Agricultural Area (UAA) (FiBL, 2019; Eurostat, 2019; DGADR, 2019; INE, 2019; GPP, 2019). This growth has been seen in terms of production, number of producers, amount of retail sales, imports and exports. This article attempts to build on the Multi-Level Perspective (MLP) and Socio-Technological (ST) transitions theory by employing a whole systems analysis (Geels, 2018) of organic agriculture in Portugal, which defends an integrated vision of the systems, where multiple interactions occur within and among the landscape, the regime and the niche levels. This approach has been employed in order to develop a critical analysis of the current state of the Portuguese organic agriculture sector, stressing the multiciplity of elements that are contributing to the agro-food system´s transformation into a more sustainable one.